The Effect of Government Investment and Private Investment on Job Opportunities and Unemployment in North Sumatra Province - Rika Damayanti; Nova Bella Prastika; Siti Kamariah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine how big the influence of Government Investment and Private Investment on Job Opportunities and Unemployment in North Sumatra Province. The type of research conducted in this research is quantitative research, namely research methods that use quantitative descriptive. In analyzing the data, the path analysis method was used in measuring the magnitude of the effect shown by the route coefficient on each route chart from the causal relationship between the variables of private investment and government investment on employment opportunities and the consequences for unemployment. Path analysis is used to analyze the relationship between variables with the aim of identifying the direct and indirect effects of causal variables on an affected variable.